Peran Keluarga sebagai Mediator dalam Pengaruh Media Sosial terhadap Perilaku Prososial dan Agresi Remaja: Sebuah Tinjauan Sistematis (SLR) - Anik Dwi Hiremawati; Anenda Bagus Satrya Ganesha (Universitas Kristen Maranatha, 2025)
The development of social media in adolescents' lives can encourage prosocial behavior through interaction and empathetic expression. However, it also risks triggering aggression due to exposure to harmfull content and unhealthy interactions. This study aims to systematically examine how the role of family mediates the impact of social media on prosocial and aggressive tendencies in adolescents. This study was conducted using a Systematic Literature Review (SLR) approach using the PRISMA 2020 guide. The literature search process was conducted on June 24-30,2025, in five main databases: Google Scholar, Scopus, PubMed, ScienceDirect, and Mendeley. The selection was made for articles published in 2018-2024, including peer-reviewed journal articles in Indonesian or English. Fourteen articles that met the inclusion criteria were analyzed thematically. Findings show that emotional support from families, open communication, and positive supervision of digital media use contribute to shaping prosocial behaviors and lowering aggressive tendencies in adolescents. Families who are actively involved in adolescents' online activities tend to be able to direct them to healthy social interactions. The role of the family has proven to be crucial in shaping adolescents' social behavior through supportive supervision and open communication. Based on attachment theory and social control theory, families foster positive norms, strengthen emotional cohesion, and increase resistance to social pressure and exposure to harmfull content from social media. Family interventions, such as digital literacy and maintaining effective communication of social values, can stimulate prosocial behavior and prevent the emergence of aggressive behavior. Thus, the family plays a positive role as a mediator in respondimg to social challenges in the digital era.